Canning of "Adobong Hito" (Clarias Batrachus Linn.) - Santos, Elvira A.; Alabastro, Estrella F. (1975.)
This study was undertaken to develop the specifications for canning of "adobong hito." A satisfactory recipe was formulated by varying the salt concentrations (1.3 and 1.5%), vinegar concentration (10% and 12 %), and pre-cooking methods (frying and boiling). A 1.3% salt and 12% vinegar level and pre-cooking by boiling were chosen. To determine an adequate processing time and temperature, combinations of 250°F for 45 minutes, 240°F for 45 minutes and 250°F for 30 minutes were tried. Based on the result s of the heat penetration studies, physico-chemical and cut-out tests, microbiological tests and sensory evaluation of the canned products, processing time and temperature of 30 minutes at 250°F was established to be the best of the three combinations studied.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Catfishes; Canned fish; Cookery (Catfish)